Autistic traits in synaesthesia: atypical sensory sensitivity and enhanced perception of details. (9th December 2019) - van Leeuwen, Tessa M.; van Petersen, Eline; Burghoorn, Floor; Dingemanse, Mark; van Lier, Rob
Abstract : In synaesthetes, specific sensory stimuli (e.g. black letters) elicit additional experiences (e.g. colour). Synaesthesia is highly prevalent among individuals with autism spectrum disorder (ASD), but the mechanisms of this co-occurrence are not clear. We hypothesized autism and synaesthesia share atypical sensory sensitivity and perception. We assessed autistic traits, sensory sensitivity and visual perception in two synaesthete populations. In Study 1, synaesthetes ( N = 79, of different types) scored higher than non-synaesthetes ( N = 76) on the Attention-to-detail and Social skills subscales of the autism spectrum quotient indexing autistic traits, and on the Glasgow Sensory Questionnaire indexing sensory hypersensitivity and hyposensitivity which frequently occur in autism. Synaesthetes performed two local/global visual tasks because individuals with autism typically show a bias towards detail processing. In synaesthetes, elevated motion coherence thresholds (MCTs) suggested reduced global motion perception, and higher accuracy on an embedded figures task suggested enhanced local perception. In Study 2, sequence-space synaesthetes ( N = 18) completed the same tasks. Questionnaire and embedded figures results qualitatively resembled Study 1 results, but no significant group differences with non-synaesthetes ( N = 20) were obtained. Unexpectedly, sequence-space synaesthetes had reduced MCTs. Altogether, our studies suggest atypical sensory sensitivity and a bias towards detail processing are shared features of synaesthesia and ASD. This article is part of the discussion meeting issue 'Bridging senses: novel insights from synaesthesia'.